SHUFFLING BEFORE LOADING TERHADAP KECEPATAN MUAT PETIKEMAS - Dian Cristopher Anggara; Humairo Humairo; Berlian Badarusman (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2017)
The purpose of this research is to find out the effect of shuffling before loading to the containers’ loading speed. This research method used simple regression based on functional or causal relationship of one independent variable with one dependent variable. Simple linear regression analysis is a linear relation between one independent variable (X) with the dependent variable (Y). Koja Container Terminal is the first container terminal in Indonesia operated by both the government and private company that aimed at contributing to the growth of the country. There is a moderate relationship between variable X (shuffling before loading) to variable Y (container loading speed) at Koja Container Terminal in 2015 with r value of 0.561 based on coefficient interpretation with value 0.40-0,599.